Electronic Properties And Gas Adsorption Behaviour Of Pristine, Silicon-, And Boron-Doped (8, 0) Single-Walled Carbon Nanotube : A First Principles Study - Mohd Abid, Mohd Asyadi Azam; Alias, Farizul Muiz; Liew, Weng Tack; Raja Seman, Raja Noor Amalina; Mohamad Taib, Mohamad Fariz (Elsevier, 2017)
-